Psychological Impact Assessment in Patients with Noncommunicable Diseases during COVID-19 Pandemic through Validated Fear of COVID-19 scale: A Cross-Sectional Online Survey - Ponnam, Hima B.; Akondi, Butchi R.; Jagadabhi, Santosh K.; Koppula, Divya T.; Konduru, Shanmukha P. (Journal of Health and Allied Sciences NU, 2022)
Background The novel coronavirus disease 2019 (COVID-19) pandemic has created immense panic globally with its advent in December 2019 and now showing readvent with its camouflage of different dangerous mutant strains. Its psychological repercussions on the community are very disastrous and immeasurable. At this juncture, the most vulnerable group are the patients of Noncommunicable diseases (NCDs) who are the most sufferers due to the impact caused by the anxiety and fear of COVID-19 apart from its high rate of infectivity. In this context, an online survey to assess the levels of anxiety and fear of COVID-19 in patients with lifestyle diseases has been taken up.Methods This was an online cross-sectional survey using the Fear of COVID-19 Scale (FCV-19S) to assess the levels of anxiety and fear in patients with NCDs. The survey was made available for both genders and an age group of 30 years and above in India.Results and Discussion A total of 627 participants participated in this online survey. The Indian residents with NCDS )Noncommunicable diseases) were found to suffer from significantly increased levels of anxiety and fear of COVID-19 and almost 60.4% of the participants were found to acquire these lifestyle diseases as diabetes and hypertension during this recent COVID-19 times.Conclusion This survey shows the real-time psychological impact of COVID-19 which has a disastrous effect upon the community especially on the patients with NCDs who are the most vulnerable group. The study findings corroborate with the recent studies conducted on NCDs.
Keywords: COVID-19 pandemic; cross-sectional survey; FCV-19S; fear of COVID-19 scale; India; noncommunicable diseases; NCD